Effect of enzymatic interesterification on the textural and nutritional properties of a probiotic table spread containing milk fat. (April 2020) - Santos, Clara Simone dos; Kanup, Raquel Fortes; Albuquerque, Marcela Albuquerque Cavalcanti; Bedani, Raquel; Souza, Cínthia Hoch Batista de; Gioielli, Luiz Antonio; Saad, Susana Marta Isay; Ract, Juliana Neves Rodrigues
Abstract: High lipid food matrices are advantageous in protecting probiotic microorganisms during storage and also during digestion. This study aimed to apply enzymatically interesterified milk fat (MF) and palm olein (PO) blends as the fat base for the formulation of a probiotic table spread with improved melting behavior when compared to butter. Enzymatic interesterification imparted spreadability to the probiotic table spreads at room temperature, while the viability of the probiotic bacteria Bifidobacterium animalis subsp. lactis Bb-12, which ranged from 8 to 9 log CFU/g during 28 days, was not affected. The mean B. animalis Bb-12 populations under in vitro simulated gastrointestinal conditions were kept between 5.5 and 8.7 log CFU/g. Hence, these table spreads revealed to be a suitable food matrix for the incorporation of B. animalis Bb-12 and interesterification combined with the addition of PO improved textural and nutritional properties by increasing the unsaturation level of the fat base. Highlights: Palm olein improved milk fat nutritional properties due to increased unsaturation. Products were all well accepted by consumers, with a high proportion of scores 7-8. Enzymatic interesterification imparted spreadability to the probiotic table spreads. Probiotic viability and GI in vitro survival were not affected by interesterification.